Stock Split Impact: Analyzing Price and Return Changes in the Capital Market: Dampak Pembagian Saham: Analisis Perubahan Harga Saham dan Imbal Hasil di Pasar Modal - Inka Ayu Suhartini; Wiwit Hariyanto (Academia Open, 2022)
This study investigates the effect of stock splits on stock prices and stock returns in the capital market. Drawing from the trading range theory and signaling theory, the research analyzes daily data over a five-year period (2015-2020) for 31 purposively sampled companies. The analytical methods employed include descriptive statistics, normality tests, and paired sample t-tests. The findings reveal significant differences in both stock prices and stock returns before and after stock splits. The results emphasize the significance of stock splits as a potential catalyst for financial changes in the market, holding implications for investors and market participants in their decision-making processes. Highlights: The study analyzes the impact of stock splits on stock prices and returns in the capital market. The research focuses on the trading range theory and its implications for stock splits. The findings highlight significant differences in stock prices and returns before and after stock splits, emphasizing the financial effects of these events in the market. Keywords: stock split, stock prices, stock returns, capital market, trading range theory.